Pengaruh Model Pembelajaran Quantum Teaching Terhadap Kepercayaan Diri Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di UPT SMP Negeri 17 Medan - Rina Susanti; Zulham Zulham (Jayapangus Press, 2025)
This study aims to determine the effect of the Quantum Teaching learning model on students' self-confidence in Islamic Religious Education subjects. The method used is quantitative with a quasi-experimental approach and a Non-Equivalent Control Group Design. The research sample consisted of two classes, namely the experimental class that was treated with the Quantum Teaching model and the control class that used conventional learning, each consisting of 32 students. The research instrument used was a Likert scale questionnaire to measure the students' level of self-confidence. The results of the descriptive analysis show that the average self-confidence score of students in the experimental class increased from 42.00 to 60.09, while in the control class it only increased from 41.94 to 45.94. The normality test indicated that the data was not normally distributed, thus the analysis continued with non-parametric tests. The results of the Wilcoxon test showed a significant increase in each group. Meanwhile, the Mann-Whitney test showed a very significant difference between the experimental and control classes with a significance value of 0.000 (p < 0.05). A significant difference was found between student learning outcomes in the experimental and control classes. This indicates that the Quantum Teaching approach has a positive and significant impact on improving student learning outcomes compared to conventional learning methods. These findings indicate that the Quantum Teaching model is not only effective in improving cognitive understanding but also significantly increases student self-confidence. The interactive and enjoyable learning environment makes students feel valued, more active, and more confident in their abilities. Therefore, this model is recommended as an innovative and enjoyable learning alternative, particularly in teaching Islamic Religious Education.